Development and validation of a smoking rationalization scale for male smokers in China. (March 2020) - Huang, Xinyuan; Fu, Wenjie; Zhang, Haiying; Li, Hong; Li, Xiaoxia; Yang, Yong; Wang, Fan; Gao, Junling; Zheng, Pinpin; Fu, Hua; Ding, Ding; Chapman, Simon
The purpose of this study is to develop a smoking rationalization scale for Chinese male smokers. A total of 35 focus groups and 19 one-on-one interviews were conducted to collect items of the scale. Exploratory factor analyses and confirmatory factor analyses were conducted to identify the underlying structure of the scale. Results found a 26-item scale within six dimensions (smoking functional beliefs, risk generalization beliefs, social acceptability beliefs, safe smoking beliefs, self-exempting beliefs, and quitting is harmful beliefs). The scale showed acceptable validity and reliability. Results highlight that smoking rationalization is common among Chinese male smokers, and some beliefs of smoking rationalization seem to be peculiar to China.